Inclusive Institutions and the Onset of Internal Conflict in Resource-rich Countries - Tim Wegenast (German Institute of Global and Area Studies (GIGA), 2010)
The literature on institutional determinants of intra-state violence commonly asserts that the presence of multiple political parties reduces the conflict potential within countries; by co-opting oppositional groups into an institutionalized political arena, dissidents would prefer parliamentarian means over violent rebellion in order to pursue their goals. The present paper shows that this proposition does not necessarily hold for fuel-abundant states. In the presence of natural resources such as oil or gas, countries exhibiting numerous non-competitive parties are actually more susceptible to internal conflict. Fortified by the establishment of legal political parties, regime opponents succumb more easily to the prospects of securing resource revenues, adopting rapacious behaviour. Fuel-related internal grievances as well as the opposition's disaffection over the lack of effective political leverage and government use of political violence provide a seemingly legitimate motive for armed rebellion. Moreover, financial means for insurgency are raised by extortion or the possibility of selling future exploitation rights to natural resources. Logit models using different estimation techniques and alternative operationalizations corroborate the proposed claim. The argumentation is further illustrated by a depiction of the Colombian case. – – Studien über die institutionellen Determinanten innerstaatlicher Gewalt legen nahe, dass die Präsenz multipler politischer Parteien das Konfliktpotential innerhalb der Länder reduziert. Es wird behauptet, dass Parteien oppositionelle Gruppierungen in eine institutionalisierte politische Arena kooptieren und somit anstatt der Anwendung gewaltsamer Rebellion die Verfolgung parlamentarischer Maßnahmen fördern. Der vorliegende Artikel zeigt, dass diese Prämisse nicht für ressourcenreiche Staaten gilt. Bei gleichzeitigem Vorhandensein von natürlichen Ressourcen wie Öl oder Gas und nicht-kompetitiver Multiparteiensysteme steigt die innerstaatliche Konfliktwahrscheinlichkeit. Gestärkt durch die Einrichtung legaler politischer Parteien und geleitet von der Absicht, die Ressourcengewinne zu kontrollieren, greifen Dissidenten eher zu Waffen. Ressourcenbezogene Missstände sowie die Unzufriedenheit Oppositioneller über mangelnde politische Einflussmöglichkeiten und die Anwendung staatlicher Unterdrückung liefern dabei offenbar legitime Motive für gewaltsame Aktionen. Zudem wird in vielen Fällen die Finanzierung rebellischer Aufstände z. B. durch ressourcenbedingte Erpressung ermöglicht. Ergebnisse von Logit-Modellen unter Anwendung unterschiedlicher Schätzverfahren und alternativer Operationalisierungen unterstreichen die vorgetragene Argumentation, welche durch die Schilderung des kolumbianischen Falls zusätzlich veranschaulicht wird.
Keywords: 300; intra-state conflict; natural resources; political parties; democracy; Colombia; Rohstoffressourcen; Parteiensystem; Parlamentarismus; Sozialer Konflikt; Politische Unruhen; Schätzung; Welt